INTERRELASI ANTARA ETIKA DAN SISTEM EKONOMI (Studi Pemikiran Ekonomi Ibnu Khaldun) - Abdul Salam (Universitas Alma Ata, 2011)
Ibn Khaldun was one of the scholars' greatest that no one doubted his dept of knowledge of Islamic religion. In the Islamic religious knowledge, he has trained by many greatest scholars since childhood moment-one of them is his father. Ibn Khaldun can also be called as a scientist who never ask and doubted the truth of Islamic law. Understanding that any observations for him, he could not be separated from the Islamic values inherent in him. Through in-depth discussion and critical of his work, will be seen in ethical view of religious that accommodate economic teachings of Islam, and other hand the human family to recognize the nature to endeavor economic activity.This type of research is the research library (library research), to describe something. Data collection techniques using qualitative methods as the research procedures to descriptive data. To analyze the data that was gathered using the deductive, using a philosophical approach.Historically there is close relationship between ethics and economics, which was originally it was part of the problem of economic ethics. Ibn Khaldun's economic notion explain a multidimensional economic concepts that involving various social aspects in the context of his thinking about the al-al-basyari'amran which describes the rise and fall of a civilization which moral decline influence in it. Ibn Khaldun's economic concept implies an economic system that requires the five components, namely Shari'ah, government , people, property, economic activity and justice, in unity.Keywords: Interrelation, ethical, economic systems, Ibn Khaldun